SEMANTICS AND FEATURES OF FUNCTIONING OF TARGET CONNECTORS OF SUBORDINATION - Ясакова, Н. Ю. (Proceedings of National Aviation University (archive), 2021)
The semantics and functioning of the means of communication of the predicative parts of a complex sentence of the purpose are considered. The target connectors and homofunctional units that have not acquired categorical features of the connector are distinguished. The dependence between the meaning of the conjunction and the semantic organization of the combined parts is established.